Figuratividade do número e simulacros do IBGE na mídia impressa - Bracco, Adelina (2007)
In this analysis we looked into news stories appearing on four Brazilian national daily newspapers Folha de S. Paulo, O Estado de São Paulo, O Globo e Jornal do Brasil during the period ranging from December 2000 to 2007, in which we could find a large number of news about official statistical data produced by Brazilian statistical bureau (IBGE) and related to Brazilian people s living conditions. The aim of this study was to identify the signification emerging from these texts as well as different modes of presence of IBGE as they were constructed by the newspapers which, for that purpose, adopted enunciative and figurativization procedures, and also find out how figurativity was capable of unleashing a series of meaning effects particularly those of objectivity, subjectivity, veridiction, veracity and fiducia (trust). The theory and methodology to achieve our aim came from discursive semiotics as it provides us with resources to analyze different structures of the news on journalistic pages starting from the most concrete and superficial level up to the deepest level and its degrees of invariance and general categories in the semionarrative dimension. Our corpus was selected following almost seven years of accompaniment and evaluation of such news with the selection of more than 60 editions of newspapers on the whole. We adopted signifying relevance criteria to achieve homogeneity as to the selected news stories so that our collection included top or highlighted stories on front pages or special inserts and some on section pages only if they proved pertinent to the analysis. The news also articulated both verbal and visual systems of expression in syncretism. Another criterion was to choose same date articles if such procedure was considered relevant to our analytical approach. The question of our research work was to understand how each newspaper bearing its own identity marks as enunciating subject developed mechanisms to build the meaning of statistical data of scientific nature and at the same time issue IBGE simulacra from their texts. Our basic hypothesis was that in their enunciations arising from Other s information (IBGE), the papers under analysis efficiently managed discursive strategies by means of which they conveyed microuniverses of axiological values to their readers as well as evaluated and sanctioned a /doing/ from alterity